1987
DOI: 10.1111/j.1399-6576.1987.tb02560.x
|View full text |Cite
|
Sign up to set email alerts
|

Bronchospasm during anaesthesia. A computer‐aided incidence study of 136 929 patients

Abstract: With the aid of a computer-based anaesthetic record-keeping system, anaesthetics complicated by bronchospasm during anaesthesia at the Karolinska Hospital were retrieved. The incidence of bronchospasm was calculated in groups characterized by various variables. In total, 246 cases of bronchospasm in 156,064 anaesthetics were retrieved. This corresponds to one case in 634 anaesthetics or 1.7 per 1000 patients. High incidence figures were seen in the age group 0-9 years (4.0/1000) when the patients showed a resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
63
0
9

Year Published

1995
1995
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(72 citation statements)
references
References 21 publications
0
63
0
9
Order By: Relevance
“…The high hospital costs imposed by this additional medical care have been described in the literature. 28 This study was designed to evaluate patients undergoing elective upper abdominal surgery, using clinical and spirometric parameters as suggested by previous studies, so as to estimate the probability of PPCs. Before doing this study, we used to assess the prognostic index on the basis of prognostic scores developed in other populations with different backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…The high hospital costs imposed by this additional medical care have been described in the literature. 28 This study was designed to evaluate patients undergoing elective upper abdominal surgery, using clinical and spirometric parameters as suggested by previous studies, so as to estimate the probability of PPCs. Before doing this study, we used to assess the prognostic index on the basis of prognostic scores developed in other populations with different backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…13 Furthermore, the airway resistance increase seen immediately after intubation in adults can be attenuated by bronchodilator administration. 15 Though adverse events during emergence from anesthesia are not common, recent URI does increase their incidence -specifically bronchospasm 1,6,7 and laryngospasm. 8,16 The role of the autonomic nervous system in laryngospasm and bronchospasm suggested a role for bronchodilator administration.…”
Section: Résultats : Dans Cette Population Spécifique Aucun Lien N'amentioning
confidence: 99%
“…In this highly selected population of afebrile patients, the results suggest that anesthesiologists may proceed with surgery using specific criteria in the presence of a URI. HE association between a recent upper respiratory tract infection (URI) and respiratory adverse events, such as bronchospasm, laryngospasm, and hemoglobin desaturation during general anesthesia, has been documented both retrospectively [1][2][3][4] and prospectively. [5][6][7][8] This is a common challenge in pediatric anesthesia, since previous studies have shown a 30-40% prevalence of recent URI in an unselected population presenting for elective surgery.…”
mentioning
confidence: 99%
“…This study is valuable in the view that it indicates the bronchospasm caused clinically by stress without using experimental induction methods. Olsson et al found the incidence of bronchospasm and wheezing as 0.17% during a general anesthesia, and they determined laringospasm incidence during general anesthesia as 0.89% in another study they conducted [23]. These retro-specific studies were done on non-asthmatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of bronchospasm may have increased the surgical procedure associated with urethral sphincter. Some previous studies have included all elective surgical procedures that have not evaluated bronchospasm in a specific surgical procedure [23,26]. Moreover; the risks possessed by the patient are also the case.…”
Section: Discussionmentioning
confidence: 99%